2020
DOI: 10.1002/ccr3.3091
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal tetanus in St. Mary’s Hospital Lacor: A case report

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…There are some case reports supporting the use of phenobarbital in generalized and neonatal tetanus, although some of them have shown no mortality benefit. 16 A meta-analysis of studies on children with tetanus reported diazepam alone is more beneficial on controlling tenues and reducing mortality than if it is combined with phenobarbital (RR of death 0.36; 95% CI 0.15-0.86; risk difference 12.22; 95% CI −0.38 to −0.06). 17 However, the combination of diazepam and phenobarbital compered to diazepam alone has demonstrated a significantly shorter clinical course and hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some case reports supporting the use of phenobarbital in generalized and neonatal tetanus, although some of them have shown no mortality benefit. 16 A meta-analysis of studies on children with tetanus reported diazepam alone is more beneficial on controlling tenues and reducing mortality than if it is combined with phenobarbital (RR of death 0.36; 95% CI 0.15-0.86; risk difference 12.22; 95% CI −0.38 to −0.06). 17 However, the combination of diazepam and phenobarbital compered to diazepam alone has demonstrated a significantly shorter clinical course and hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Since the patient's spasms began to decrease after propofol administration, and also due to the concern about the probability of propofol infusion syndrome, we decided to change it to intravenous phenobarbital, with regards to similarity in the antispasmodic mechanism of these agents. There are some case reports supporting the use of phenobarbital in generalized and neonatal tetanus, although some of them have shown no mortality benefit 16 . A meta‐analysis of studies on children with tetanus reported diazepam alone is more beneficial on controlling tenues and reducing mortality than if it is combined with phenobarbital (RR of death 0.36; 95% CI 0.15–0.86; risk difference 12.22; 95% CI −0.38 to −0.06) 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Low-resource settings continue to report high mortality from neonatal tetanus, due to lack of sophisticated management modalities like neuromuscular blockade and invasive ventilation [ 1 – 3 , 6 ]. This high mortality has especially been reported in those with symptom onset within the first week of life [ 3 , 7 ], and in our case symptoms started on the fourth day of life. Earlier presentation with disease may be due to higher inocula of C. tetani bacteria, and/or younger infants may be physiologically at higher risk of death [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal tetanus, though preventable by maternal vaccination and aseptic delivery as well as cord care, is still a common cause of morbidity and mortality in developing countries [ 1 – 3 ]. It is caused by a toxin of Clostridium tetani , a Gram-positive spore-forming anaerobe and its incubation period ranges from 3 to 10 days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation